DAYA TARIK WISATA DANAU PERINTIS SEBAGAI LOKOMOTIF PEREKONOMIAN MASYARAKAT LOKAL DI KECAMATAN SUWAWA, KABUPATEN BONE BOLANGO - Srilian Laxmiwaty Dai (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2020)
The objectives of this research is to figure out the fulfillment of tourism components at Danau Perintis Tourist Attraction and to formulate the steeps in order to build Danau Perintis Tourist Attraction as the economical locomotive of the local community. As the objectives, this research studies whether or not the tourism components which should be fulfill in atourist atraction has been fulfilled in Danau Perintis Tourit Attraction. The theory ini this research is tourism components which is consist of Attraction, Accesibility and Amenities. There are many obstacles that was found in Danau Perintis Tourist Attraction act as an economical locomotive of the local community, so that through this research and also based on the theory of this research there ara some solutions that can be recomended in order to create the act of Danau Perintis Tourist Attraction to give a positive impact for the local community financially. The result based on those three tourism components with other supporting components are; there should be an attraction development sach as water ride facilities and also a maximum maintenance. Next is from the accesibility side, this tourist attraction has a good accesibility. It means this place is accesible easily for all tourist from any areas. The last component is about amenities or facilities that should be completed.